A Study on the Impact of Working Capital Management Practices on Firms Profitability: A Comprehensive Study on the Impact of Working Capital Management Practices on the Profitability of Computer Software Companies in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Working capitalmanagement is a very important aspect of corporate Finance. The study has beenundertaken to examine the management of finance playing a crucial role in thegrowth. It is concerned with examining the structure of liquidity position andprofitability position of ten top computers –software companies in India suchas TCS, Wipro, Infosys, HCL Techno, and Techno. Mahindra, Oracle Fin Service,Mind tree, Polaris Tech., L&T InfoTech., Persistent. The research designfollowed for this study is descriptive research of the working capitalmanagement of the above sectors. For analyzing the data, an in depth researchanalysis and various statistical tools and techniques were used. The data foranalysis is collected from the financial statements published in the annualreports. It was found that the study of working capital management of thecompany is very effective and also the firm has to maintain the liquidity andsolvency position to repay its obligations in time. The purpose of thispaper is to examine the trends in working capital management and its impact onfirms’ profitability. The dependent variable, return on total assets (ROTA) isused as a measure of profitability and the relation between working capitalmanagement is investigated for a sample of 10 computer-software companies dataanalysis for the period 2009-2013.